A new method to improve the objectivity of early Six Sigma analysis. Issue 9 (3rd October 2016) - Cox, Steven; Elton, Virginia; Garside, John A.; Kotsialos, Apostolos; Marmo, João Victor; Cunha, Lorena; Lennon, Grant; Gill, Chris
Abstract : Purpose: A process improvement sampling methodology, known as process variation diagnostic tool (PROVADT), was proposed by Cox et al. (2013). The method was designed to support the objectivity of Six Sigma projects performing the measure-analyse phases of the define-measure-analyse-improve-control cycle. An issue in PROVADT is that it is unable to distinguish between measurement and product variation in the presence of a poor Gage repeatability and reproducibility (R&R) result. The purpose of this paper is to improve and address PROVADT's sampling structure by enabling a true Gage R&R as part of its design. Design/methodology/approach: This paper derives an enhanced PROVADT method by examining the theoretical sampling constraints required to perform a Gage R&R study. The original PROVADT method is then extended to fulfil these requirements. To test this enhanced approach, it was applied first to a simulated manufacturing process and then in two industry case studies. Findings: The results in this paper demonstrates that enhanced PROVADT was able to achieve a full Gage R&R result. This required 20 additional measurements when compared to the original method, but saved up to ten additional products and 20 additional measurements being taken in future experiments if the original method failed to obtain a valid Gage R&R. These benefits were highlighted in simulation and industry case studies. Originality/value: The work into the PROVADT method aims to improve the objectivity of early Six Sigma analyses of quality issues, which has documented issues.